Decimeter-level positioning in dynamic applications with a single GPS receiver - Saka, M. H.; Alkan, R. M. (Springer, 2014)
Although the ongoing GPS modernization studies provide better autonomous positioning accuracy (i.e. a few meters), this accuracy level is not enough for many surveying applications. Depending on the developments in satellite-based positioning technology and GNSS data availability and analysis techniques, some new approaches and algorithms have been proposed in the world of global positioning to enhance the autonomous positioning accuracy. In this study, a precise positioning technique, named self-differential method, is introduced using the dual frequency GPS data collected by a single geodetic-grade GPS receiver. The technique uses iono-free carrier phase observations, precise satellite ephemerides and satellite clock data. In order to validate the performance of the introduced method in a dynamic environment two kinematic tests were conducted at Halic Bay in Istanbul, Turkey. The results show that the method is capable of achieving decimeter level of positioning accuracy without the need of an additional reference station or any other data while reducing the field operational costs.
Keywords: GNSS; Kinematic GPS; Self-differential method; Absolute positioning